2019
DOI: 10.1111/pedi.12908
|View full text |Cite
|
Sign up to set email alerts
|

Lower HbA1c in patients with type 1 diabetes and celiac disease who reached celiac‐specific antibody‐negativity—A multicenter DPV analysis

Abstract: Objectives To study celiac‐specific antibody status over 3 years in patients with type 1 diabetes and biopsy‐proven celiac disease (T1D + CD). Furthermore, to determine clinical differences after diagnosis between patients reaching constant antibody‐negativity (Ab‐neg) and staying antibody‐positive (Ab‐pos). Methods A total of 608 pediatric T1D + CD patients from the multicenter DPV registry were studied longitudinally regarding their CD specific antibody‐status. Differences between Ab‐neg (n = 218) and Ab‐pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
4
10
0
2
Order By: Relevance
“…In our study worse glycemic control and the risk of experiencing DKAs was associated with poorer compliance. That better compliance is associated with a better glycemic control is in line with previous studies [28,29,32], and the only, to our knowledge, randomized controlled study (RCT) on the topic to date also found that a GFD resulted in better glycemic control [33]. In contrast with our results, the only other study on DKAs we found described no association between compliance and DKA [32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study worse glycemic control and the risk of experiencing DKAs was associated with poorer compliance. That better compliance is associated with a better glycemic control is in line with previous studies [28,29,32], and the only, to our knowledge, randomized controlled study (RCT) on the topic to date also found that a GFD resulted in better glycemic control [33]. In contrast with our results, the only other study on DKAs we found described no association between compliance and DKA [32].…”
Section: Discussionsupporting
confidence: 91%
“…In most studies, compliance was associated with better glycemic control [28,29] and/or growth [29,31]; only one found no association between compliance and growth [30]. We found one larger registry study on 608 double-diagnosed children which also reported good compliance to be associated with both better glycemic control and improved growth, but this study only found a good dietary adherence in 36% of the children [32]. Moreover a randomized controlled study comparing 15 double-diagnosed children on a GFD to 15 double-diagnosed children on a normal diet found children on a GFD to have better glycemic control after 12 months [33].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nagl et al konnten in einer Arbeit mit Teilnehmenden aus der Gruppe der Diabetes-Patienten-Verlaufsdokumentation (DPV) zeigen, dass nur ein Drittel der Patienten mit T1D + Zöliakie konstant negative AK-Titer erreichte. Diejenigen mit konstant negativen AK-Nachweisen hatten eine bessere metabolische Kontrolle [11].…”
Section: Autoimmunthyreoiditis Hypothyreote Formunclassified
“…In the same vein, recent data from the first prospective randomized clinical trial in this regard concluded there could be a decrease in hypoglycemic episodes and better glycemic control in patients with T1DM with minimally symptomatic celiac disease following a GFD. 22,23 A recent interventional trial also suggests that there might be a beneficial effect of GFD in patients with T1DM, even if they do not have celiac disease. 24 Be that as it may, in my view the issue boils down to the following: There is solid evidence that celiac disease is quite common in children and adolescents with T1DM.…”
mentioning
confidence: 99%